Bài ni t mần cho phát chán nó rồi:))
Ta có:\(x^{2012}+y^{2012}=\left(x^{2011}+y^{2011}\right)\left(a+b\right)-ab\left(a^{2010}+b^{2010}\right)\left(1\right)\)
Mặt khác:\(x^{100}+y^{100}=x^{101}+y^{101}=x^{102}+y^{102}\left(2\right)\)
Từ \(\left(1\right);\left(2\right)\Rightarrow1=x+y-xy\)
\(\Rightarrow\left(x-1\right)\left(y-1\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x=1\Rightarrow1+y^{2010}=1+y^{2011}=1+y^{2012}\Rightarrow y=1\\y=1\Rightarrow x^{2010}+1=x^{2011}+1=x^{2012}+1\Rightarrow x=1\end{cases}}\)vì \(x;y\) là các số dương
Thay vào ta được:\(A=1^{2020}+1^{2020}=2\)
Làm lại nha.sơ suất quá:((
Ta có:
\(x^{2012}+y^{2012}=\left(x^{2011}+y^{2011}\right)\left(x+y\right)-xy\left(x^{2010}+y^{201}\right)\left(1\right)\)
Mặt khác:\(x^{2010}+y^{2010}=x^{2011}+y^{2011}=x^{2012}+y^{2012}\left(2\right)\)
Từ (1);(2) suy ra:
\(x^{2010}+y^{2010}=\left(x^{2010}+y^{2010}\right)\left(x+y\right)-xy\left(x^{2010}+y^{2010}\right)\)
\(=\left(x^{2010}+y^{2010}\right)\left(x+y-xy\right)\)
\(\Rightarrow x+y-xy=1\)
\(\Rightarrow\left(x-1\right)\left(y-1\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x=1\Rightarrow1+y^{2010}=1+y^{2011}=1+y^{2012}\Rightarrow y=1\\y=1\Rightarrow1+x^{2010}=1+x^{2011}=1+x^{2012}\Rightarrow x=1\end{cases}}\)
Thay vào ta được \(A=3\)
Vậy A=3